Kebijakan Utang Jangka Panjang : Kajian Struktur Modal Entitas Terbuka Non Keuangan di Indonesia Yang Dikendalikan Keluarga - Sugiarto Sugiarto (Ultima Management : Jurnal Ilmu Manajemen, 2010)
Compared to non-family controlled firms, family controlled firms have a stronger desire to maintain control to protect their highly valuable private benefits of control and firm-specific human capital. With substantial wealth and human capital at risk, family owners tend to be more risk averse than non-family owners, and also have stronger intention to reduce the prospect of financial distress and bankruptcy. These unique characteristics of family firms potentially make their capital structure decisions different from those of non-family firms. Panel data from 137 publicly listed firms in Indonesia from 1996 to 2005 were used to investigate the impact of family control on capital structure, particularly on debt maturity decisions. Keywords: Family controlled firms, capital structure decisions, debt maturity